Drgania Przypadkowe Oscylatora Harmonicznego Wywołane Pewnym Prawie Stacjonarnym Procesem Losowym - Tylikowski, A.; Kawulok, S. (Engineering Transactions, 1970)
In this paper is analysed the influence of uneveness of the shaft guides upon the vibrations of a hoisting vessel considered to be a harmonic oscillator. The correlation function of the uneveness of the guides is determined, and appears, in general, to be a non-stationary random process. In the further considerations, that function is approximated by an almost stationary process, as understood by the Kempe de Feriet definition. The spectral density is calculated for the process thus assumed.The spectral density and variance of the initial function (of radiation) has been obtained for a harmonic oscillator subjected to kinematic forcing in a mobile and immobile system of reference.